Efficacy and Safety of Neoadjuvant Gemcitabine Plus Nab-Paclitaxel in Borderline Resectable and Locally Advanced Pancreatic Cancer—A Systematic Review and Meta-Analysis - Damm, Marko; Efremov, Ljupcho; Birnbach, Benedikt; Terrero, Gretel; Kleeff, Jörg; Mikolajczyk, Rafael; Rosendahl, Jonas; Michl, Patrick; Krug, Sebastian (Cancers, 2021)
Therapy with gemcitabine and nab-paclitaxel (GNP) is the most commonly used palliative chemotherapy, but its advantage in the neoadjuvant setting remains unclear. Accordingly, our aim is to evaluate the impact of first-line neoadjuvant therapy with GNP in patients with borderline resectable (BRPC) and locally advanced pancreatic cancer (LAPC). A systematic search for published studies until August 2020 was performed. The primary endpoint included resection and R0 resection rates in the intention-to-treat population. Secondary endpoints were response rate, survival and toxicity. Among 21 studies, 950 patients who received neoadjuvant GNP were evaluated. Treatment with GNP resulted in surgical resection and R0 resection rates as follows: 49% (95% CI 30–68%) and 36% (95% CI 17–58%) for BRPC and 16% (95% CI 7–26%) and 11% (95% CI 5–19%) for LAPC, respectively. The objective response rates and the median overall survival (mOS) ranged from 0 to 67% and 12 to 30 months, respectively. Neutropenia (range 5–77%) and neuropathy (range 0–22%) were the most commonly reported grade 3 to 4 adverse events. Neoadjuvant chemotherapy with GNP can be performed safely and with valuable effects in patients with BRPC and LAPC. The utility of GNP in comparison to FOLFIRINOX in the neoadjuvant setting requires further investigation in prospective randomized trials.